The nexus between mining production and economic growth in South Africa - Nhlangwini, Pamela; Mongale, Itumeleng Pleasure (Penerbit Universiti Kebangsaan Malaysia, 2019)
The production crisis in the mining sector is a great concern to the South African economy. This happens regardless of the policies and implementation of investment strategies that the government has put in the industry, which still has a steady contribution to the gross domestic product. The aim of this study was to investigate the relationship between mining production, government expenditure and economic growth in South Africa. As a resource-endowed country that depends primarily on minerals to enhance growth, the operation in mining production is crucial. The paper employed the vector error correction model to analyze the annual time series data from the South African Reserve Bank covering the period 1983 to 2015. Preliminary results show that all variables were found to be stationary at first difference. Subsequently, the cointegration results indicated that there was at least one cointegrating equation, which confirmed the existence of a long-run relationship in the system. The long-run analysis showed that mining production excluding gold has a significant coefficient compared to all other variables, and has a positive relationship with expenditure on gross domestic product. The mining production of gold showed a negative relationship with expenditure on the gross domestic product, which supports the ‘resource curse’ theory. Finally, the short-run analysis showed that the system will come back to equilibrium. The study recommends that policymakers should formulate policies that will encourage and attract both local and international investors in this industry, especially in mining production excluding gold.